Свобода та сваволя у практиці повсякдення - Стежко, З. В.; Stezhko, Z. (ЦНТУ, 2023)
Метою роботи є висвітлення специфіки співвідношення лексем «свобода» та «сваволя» у сучасному суспільстві. Виділено атрибутивні характеристики лексеми «свобода» на категоріальному, понятійному та ментально-ціннісному рівнях, а також атрибутивні характеристики лексеми «сваволя». Вказано, що ототожнення категорії «свобода» та поняття «сваволя» є сутнісною причиною тотальної поведінкової девіації сучасної молоді. Запропоновано новий дискурс аналізу даної проблеми. The aim of the paper is to demonstrate the specifics of relationships between the tokens "freedom" and "arbitrariness" in modern society. The attributive characteristics of the lexeme "freedom" at the categorical, conceptual, and mental-value (common sense) levels, as well as the attributive characteristics of the lexeme "arbitrariness" are highlighted. It is noted that the identification of the category "freedom" and the concept of "arbitrariness" is the essential cause of the total behavioral deviation of modern youth. A new discourse of analysis of this problem is proposed.
Keywords: свобода; необхідність; сваволя; відносність; відповідальність; девіація; freedom; arbitrariness; relativity; responsibility; necessity; deviation